2017
DOI: 10.1097/j.pain.0000000000001057
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA–mediated downregulation of potassium-chloride-cotransporter and vesicular γ-aminobutyric acid transporter expression in spinal cord contributes to neonatal cystitis–induced visceral pain in rats

Abstract: Loss of GABAergic inhibition in pain pathways has been considered to be a key component in the development of chronic pain. In the present study, we intended to examine whether miR-92b–mediated posttranscriptional dysregulation of spinal potassium chloride cotransporter (KCC2) and vesicular γ-aminobutyric acid transporter (VGAT) plays a major role in the development and maintenance of long-term visceral hyperalgesia in neonatal zymosan–treated rats. Neonatal cystitis was induced by transurethral zymosan admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…Knockdown of KCC2 by intrathecal administration of KCC2-siRNA reduces inhibitory synaptic transmission (Lin et al 2017 ). mRNA-mediated downregulation of KCC2 and vesicular GABA transporter expression in the spinal cord contribute to visceral pain in rats (Zhang et al 2017 ). Dynamic changes in the mRNA profile revealed multiple regulatory mechanisms in spinofugal projection neurons (von Schack et al 2011 ).…”
Section: Dorsal Horn and Nociceptionmentioning
confidence: 99%
“…Knockdown of KCC2 by intrathecal administration of KCC2-siRNA reduces inhibitory synaptic transmission (Lin et al 2017 ). mRNA-mediated downregulation of KCC2 and vesicular GABA transporter expression in the spinal cord contribute to visceral pain in rats (Zhang et al 2017 ). Dynamic changes in the mRNA profile revealed multiple regulatory mechanisms in spinofugal projection neurons (von Schack et al 2011 ).…”
Section: Dorsal Horn and Nociceptionmentioning
confidence: 99%
“…As a negative regulator of transient receptor potential cation channel subfamily V member 1 (TRPV1) expression, miR-199 expression in colonic biopsies was negatively correlated with visceral pain scores and TRPV1 expression in diarrhea-predominate IBS patients (Zhou Q. et al, 2016 ). Preclinical studies in rat models examined miRNA expression in the spinal cord and identified miR-17-5p as a possible mediator of water avoidance stress-induced colonic hypersensitivity (Sengupta et al, 2013 ; Bradesi et al, 2015 ; Zhang et al, 2017 ). In summary, life experiences along with a person's genetic make-up determines their vulnerability or resilience to developing chronic stress-induced pain disorders such as IBS.…”
Section: Epigenetic Mechanisms Mediating Stress-induced Chronic Viscementioning
confidence: 99%
“…Loss of these two ion transport channels interfered with GABA-mediated inhibition of pain signaling 112. Administration of a miR-92-3p sponge (a miRNA inhibitor) to the spinal cord of these animals reversed visceral hypersensitivity, highlighting the importance of miR-mediated mechanisms 112. Detrimental effects of prenatal, neonatal, and adult stress (top-down mechanism) on spinal cord neurons have been described by other investigators.…”
mentioning
confidence: 84%
“…For instance, the upregulation of miR-92-3p caused the downregulation of KCC2 and VGAT in the lumbosacral spinal cord. Loss of these two ion transport channels interfered with GABA-mediated inhibition of pain signaling 112. Administration of a miR-92-3p sponge (a miRNA inhibitor) to the spinal cord of these animals reversed visceral hypersensitivity, highlighting the importance of miR-mediated mechanisms 112.…”
mentioning
confidence: 99%